(untitled) (The Pakistan Development Review, 2001)
Money, income, and prices are important macroeconomic variables that play a crucial roles in an economy. The trends in money supply, movements in prices, changes in nominal and real income, as well as their interrelationships affect the economic life and well-being of a nation. The compilation of data on these magnitudes over long periods of time along with the supporting analysis is what constitutes monetary history. The present book by P. R. Brahmananda has carried out such an exercise for India. In presenting the monetary history of India, the author has kept the pioneering work of Milton Friedman and Anna Shwartz as a model for his work, and has comprehensively treated the 19th century events and experiences of the then Indian Subcontinent in the monetary and related areas. In the process, more than 200 time series of different variables have been brought together. The book not only contains a narrative account including the summary of the various viewpoints before the currency committees, and a detailed chronology of the period, but also examines the pros and cons of the various controversies of that period. Moreover, it subjects the empirical evidence to econometric testing of several important hypotheses of the modern-day monetary theory.